Maqasid al-Shari'ah for Green Business Oversight: Addressing Greenwashing by Design in Indonesia’s Energy Transition - Aji Baskoro (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2025)
Abstract: Greenwashing by design refers to structural misrepresentation embedded within energy transition policies, project planning, and corporate disclosure mechanisms. This phenomenon exposes limitations in sustainability governance in Indonesia’s energy sector, since ESG based regulatory instruments often privilege procedural compliance and quantitative indicators while overlooking deception rooted in policy design and regulatory architecture. This article proposes Maqāṣid al-Sharīʿah (objectives of Islamic law) as a normative ethical framework for evaluating sustainability claims beyond formal compliance, with analytical attention to intention, systemic harm, and distributive justice. Methodologically, the study applies a normative legal research design that combines conceptual and philosophical approaches and relies on secondary sources, including doctrinal Islamic legal texts, critical literature on sustainability governance, and contemporary scholarship on green economics and environmental ethics. Inductive mapping of greenwashing by design practices is integrated with a deductive construction of a maqāṣid-based evaluative model to show how Islamic legal theory can be operationalized for sustainability oversight. Findings indicate that maqāṣid integration shifts greenwashing assessment from a technical issue of disclosure accuracy toward an ethical problem of governance design and accountability. Arguments of this article also repositions maqāṣid al-sharīʿah as a critical normative theory of regulatory governance in Muslim majority settings, strengthening debates on green business regulation. Conceptual scope and the absence of empirical validation remain limitations, so future research should test institutional implementation and sector specific regulatory mechanisms. Abstrak: Fenomena greenwashing by design merujuk pada praktik misrepresentasi yang ditanamkan sejak tahap perancangan kebijakan transisi energi, perencanaan proyek, hingga mekanisme pelaporan korporasi. Berbagai kajian tentang tata kelola menunjukkan instrumen ESG (environmental, social, governance) sering menekankan kepatuhan prosedural dan indikator kuantitatif, sehingga kurang peka terhadap penyesatan yang bekerja pada tingkat desain kebijakan dan arsitektur regulasi. Artikel ini mengajukan Maqāṣid asy-Syarīʿah sebagai kerangka etik normatif untuk menilai klaim keberlanjutan melampaui kepatuhan formal, melalui perhatian pada niat, kerusakan sistemik, dan keadilan distributif di sektor energi Indonesia. Penelitian menerapkan metode yuridis normatif melalui pendekatan konseptual dan filosofis, berbasis sumber sekunder berupa teks doktrinal hukum Islam, kajian kritis tata kelola keberlanjutan, serta literatur ekonomi hijau dan etika lingkungan. Analisis menggabungkan pemetaan induktif pola greenwashing by design dengan konstruksi deduktif model evaluasi berbasis maqāṣid, guna menunjukkan cara pengoperasian teori hukum Islam sebagai perangkat pengawasan. Hasil kajian memperlihatkan integrasi prinsip maqāṣid menggeser isu greenwashing dari persoalan teknis akurasi pelaporan menjadi problem etis pada desain tata kelola dan akuntabilitas. Kontribusi teoretis memposisikan ulang maqāṣid sebagai teori normatif kritis bagi tata kelola regulatif pada masyarakat mayoritas Muslim, sedangkan kontribusi praktis menawarkan kerangka evaluasi berbasis nilai untuk reformasi regulasi. Batasan studi terletak pada sifat konseptual dan ketiadaan verifikasi empiris, sehingga riset lanjutan perlu menguji implementasi kelembagaan dan mekanisme regulatif sektoral yang lebih operasional.